Novel 3-fluoro-4-morpholinoaniline derivatives: synthesis and assessment of anti-cancer activity in breast cancer cells - More, Namita A.; Jadhao, Nitin L.; Meshram, Rohan J.; Tambe, Prajakta; Salve, Rajesh A.; Sabane, Jagjivan K.; Sawant, Sanskruti N.; Gajbhiye, Virendra; Gajbhiye, Jayant M. (Journal of Molecular Structure, 2022)
Heterocyclic morpholine compounds are well-known for their anti-cancer activity. In this study, novel morpholine and its sulfonamide derivatives were designed and synthesized as potential anti-tumor agents. The new compounds were obtained from amine derivatives via nucleophilic addition reactions, providing the desired products in 70 to 90% yield. The docking analysis was performed for all thirty-one compounds. Out of them, we represent the docking poses for compounds NAM-5 and NAM-7 as representatives. After docking analysis, compounds NAM-5 and NAM- 7 were tested for in vitro antitumor activity against breast cancer cell lines (MCF-7 and MDA-MB-231) and healthy mouse embryonic fibroblast cell line (3T3L-1). Amongst these, sulfonamide group-containing compound NAM-5 showed significant anti-proliferative activity with IC50 of 1.811 mu M and 2.143 mu M for MCF-7 and MDA-MB-231 cells, respectively. On the other hand, NAM-7 showed good anti-proliferative activity against MCF-7 (IC50 1.883 mu M) but slightly lower activity against MDA-MB-231 cells (IC50 4.688 mu M). The activity of both the compound was also tested on 3T3L-1 Cell line which showed activity similar to clinically approved anti-cancer drug doxorubicin (DOX). The cell death analysis by flow-cytometry confirmed apoptosis mediated cell death in 3T3L-1, MCF-7 and MDA-MB-231 cells when treated with the NAM-5 and NAM-7, respectively. The results demonstrated that the synthesized sulfonamide derivatives have significant potential as anti-cancer agents and have a substantial importance in cancer therapeutics with favourable safety profile. Structural analysis of docked poses of sulfonamide derivatives attempts to shed light on the structural basis of sulfonamide derivatives based anti-cancer effect. (C) 2021 Elsevier B.V. All rights reserved.
Keywords: Anticancer activity; Apoptosis; Breast cancer; Heterocyclic compounds; Morpholine; Sulfonamide